WorldCursor: Pointing in Intelligent Environments with a Tele-operated Laser Pointer - Wilson, Andy (UIST '03 - Adjunct Proceedings of the 16th annual ACM Symposium on User Interface Software and Technology, 2003)
We introduce the WorldCursor, a pointing device and cursor designed for intelligent environments. The WorldCursor is analogous to the mouse and cursor used in traditional GUIs: the user may select and interact with a physical device by positioning the cursor on the device and clicking. We use the XWand as a physical pointing mechanism, and couple it with the WorldCursor device which projects a cursor on the physical environment. The WorldCursor improves upon the XWand by removing the need for external positioning technology such as video cameras.